Patient‐Derived Organoids Can Guide Personalized‐Therapies for Patients with Advanced Breast Cancer - Ping Chen (Wiley, 2021)
Abstract Most breast cancers at an advanced stage exhibit an aggressive nature, and there is a lack of effective anticancer options. Herein, the development of patient‐derived organoids (PDOs) is described as a real‐time platform to explore the feasibility of tailored treatment for refractory breast cancers. PDOs are successfully generated from breast cancer tissues, including heavily treated specimens. The microtubule‐targeting drug‐sensitive response signatures of PDOs predict improved distant relapse‐free survival for invasive breast cancers treated with adjuvant chemotherapy. It is further demonstrated that PDO pharmaco‐phenotyping reflects the previous treatment responses of the corresponding patients. Finally, as clinical case studies, all patients who receive at least one drug predicate to be sensitive by PDOs achieve good responses. Altogether, the PDO model is developed as an effective platform for evaluating patient‐specific drug sensitivity in vitro, which can guide personal treatment decisions for breast cancer patients at terminal stage.